(untitled) - Rogers, Bruce (Thành phố Hồ Chí Minh, 2000)
This book is an easy and effective way to prepare for the Toefl test. It offers a step-by-step program that helps you improve not only your test-taking strategies, but also your language skills.
Keywords: English language,English language,English language,Test of english as a foreign language; Examinations,Study guides,Study and teaching,Textbooks for foreign speakers,Study guides